Проблема резистентності рослин до гербіцидів: генетичний та метаболічний аспекти - Гуральчук, Ж.З.; Мордерер, Є.Ю. (Фактори експериментальної еволюції організмів, 2015)
Aims. The plant resistance to herbicides is a big problem of modern agriculture. Thus, knowledge of the mechanisms of
resistance to herbicides is very important due to the emergence of a large number of herbicide-resistant weeds. Results.
Analysis of the literature data shows a signifi cant contribution of gene mutations to the evolution of resistance. Metabolic
processes are important too, due to enhanced metabolic capacity to detoxify herbicides. Conclusions. Some progress in
understanding the mechanisms of plant resistance to herbicides achieved, but further studies of phytopathogenesis of
herbicides and processes that occur at the molecular genetic and metabolic levels and are involved in the formation of
plant resistance to herbicides are needed.
Keywords: herbicide, resistance, target-site resistance, non-target-site resistance.